Blue Luminescence from N-doped Graphene - Lin, Shu-Yu; Chou, Sheng-Lung; Huang, Tzu-Ping; Lin, Meng-Yeh; Chen, Hui-Fen; Sarre, Peter J.; Tseng, Chien-Ming; Wu, Yu-Jong (The Astrophysical journal, 2024)
Blue luminescence (BL) has been observed in various astrophysical environments, such as the inner region of the Red Rectangle Nebula. It has been previously linked to small polycyclic aromatic hydrocarbons. In this study, we explore the potential of N- and O-doped graphene material as carriers of BL. Using vacuum ultraviolet irradiation, pristine single-layer graphene films were exposed to solid N 2 and O 2 at low temperatures, resulting in the formation of N- or O-doped graphene. The photoluminescence (PL) spectrum of the synthesized N-doped graphene exhibits an asymmetrical peak at 378 nm, which is nearly identical to the BL observed in the Red Rectangle. In contrast, the synthesized O-doped graphene shows a symmetrical PL band at 414 nm. Further Raman and X-ray photoelectron spectroscopy analyses reveal that nitrogen atoms substitute carbon atoms in the graphene lattice, introducing structural defects and sp 2 regions responsible for the observed luminescence. The simplicity of the bonding structures in the N-doped graphene, dominated by pyrrolic-N and pyridinic-N groups, further supports its potential as a model system for studying BL.